2021
DOI: 10.1177/15589447211006857
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Tendon and Nerve Gliding Exercises in the Treatment of Patients With Mild Idiopathic Carpal Tunnel Syndrome: A Randomized Controlled Trial

Abstract: Background There is limited evidence regarding the efficacy of different treatment options in patients with carpal tunnel syndrome (CTS). This study aimed at assessing the effectiveness of nerve and tendon gliding exercises in the treatment of patients with mild CTS. Methods The current prospective, randomized trial with pretest-posttest design was conducted on 80 patients with mild CTS randomly assigned to 2 groups. The treatment group was instructed to perform gliding exercises in addition to the wrist splin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In a recent, randomized controlled study of 80 patients, the study group was applied with tendon and gliding exercises together with a wrist splint, and the control group was treated with a wrist splint only. A certain amount of improvement was seen in symptom severity and the functional status scores in both groups, and it was reported that the exercises provided no extra benefit to the wrist splint treatment (8). In contrast, Hamzet et al reported that the combination of neuromobilisation techniques with exercises compare to only home exercises was more effective in improving clinical findings (26).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a recent, randomized controlled study of 80 patients, the study group was applied with tendon and gliding exercises together with a wrist splint, and the control group was treated with a wrist splint only. A certain amount of improvement was seen in symptom severity and the functional status scores in both groups, and it was reported that the exercises provided no extra benefit to the wrist splint treatment (8). In contrast, Hamzet et al reported that the combination of neuromobilisation techniques with exercises compare to only home exercises was more effective in improving clinical findings (26).…”
Section: Discussionmentioning
confidence: 98%
“…As part of soft tissue mobilisation, the myofascial release was applied to the anterior, mid, and posterior scalene, the pectoralis major and minor, the biceps brachii muscles, and the flexor retinaculum. For joint mobilisation, cervical tractions and mobilisation were applied to the distal and proximal radio-ulnar, radiocarpal (Figure 2), and intercarpal joints (6)(7)(8)9). While the patient was in supine position, general, and segmental traction to the cervical region was applied by the physiotherapist taking the patient's head in one hand and applying traction to all the cervical vertebrae, first as general than as segmental to each cervical segment starting from caudal to cranial.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations